Systematic literature review: Utilization of the ProProfs Brain Games Website to improve student learning outcomes - Rusminah Rusminah; Hamsi Mansur; Agus Hadi Utama (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2026)
Advancements in educational technology have encouraged the utilization of interactive digital learning media, one of which is the ProProfs Brain Games platform. This study aims to analyze the utilization and effectiveness of ProProfs Brain Games in improving student learning outcomes through a Systematic Literature Review (SLR) approach. A total of 11 scholarly articles published between 2020 and 2025 were analyzed using the SLR method, drawing on data sources from Google Scholar and Publish or Perish, based on predefined inclusion and exclusion criteria. The synthesis results indicate that the use of ProProfs Brain Games consistently contributes positively to the improvement of learning outcomes, student motivation, active engagement, and conceptual understanding across various educational levels and subject areas. This platform effectively supports game-based learning through interactive features such as quizzes, crossword puzzles, and online assessments. Theoretically, these findings reinforce the concept of game-based learning and the integration of digital technology as a student-centered instructional strategy. Practically, the results imply the importance of integrating interactive digital media such as ProProfs Brain Games in the implementation of the Merdeka Curriculum to create more meaningful, adaptive, and learner-oriented learning experiences in the digital era. Abstrak. Kemajuan teknologi pendidikan mendorong pemanfaatan media pembelajaran digital yang interaktif, salah satunya melalui platform ProProfs Brain Games. Penelitian ini bertujuan untuk menganalisis pemanfaatan dan efektivitas ProProfs Brain Games dalam meningkatkan hasil belajar peserta didik melalui pendekatan Systematic Literature Review (SLR). Sebanyak 11 artikel ilmiah yang diterbitkan pada periode 2020–2025 dianalisis menggunakan metode SLR dengan basis data Google Scholar dan Publish or Perish, berdasarkan kriteria inklusi dan eksklusi yang telah ditetapkan. Hasil sintesis menunjukkan bahwa penggunaan ProProfs Brain Games secara konsisten berkontribusi positif terhadap peningkatan hasil belajar, motivasi, keterlibatan aktif, serta pemahaman konseptual peserta didik pada berbagai jenjang dan mata pelajaran. Media ini efektif mendukung pembelajaran berbasis permainan (game-based learning) melalui fitur interaktif seperti kuis, teka-teki silang, dan evaluasi daring. Secara teoretis, temuan penelitian ini memperkuat konsep game-based learning dan pemanfaatan teknologi digital sebagai strategi pembelajaran yang berpusat pada peserta didik. Secara praktis, hasil penelitian ini berimplikasi pada pentingnya integrasi media digital interaktif seperti ProProfs Brain Games dalam implementasi Kurikulum Merdeka untuk menciptakan pembelajaran yang lebih bermakna, adaptif, dan sesuai dengan karakteristik peserta didik di era digital.